Renal function: water balance - Briffa, Jessica (Henry Stewart Talks, 2024)
Water balance, Effect of plasma osmolarity on vasopressin secretion, Effect of extracellular fluid volume on vasopressin secretion, Water reabsorption along the nephron, Osmolarity changes along the nephron, Vasopressin mediated water reabsorption, Urine concentration in the collecting duct